Preliminary report of clinical experience with metal-on-highly-crosslinked-polyethylene hip resurfacing. Issue 10 (October 2019) - Treacy, Ronan B. C.; Holland, James P.; Daniel, Joseph; Ziaee, Hena; McMinn, Derek J. W.
Abstract : Objectives: Modern metal-on-metal (MoM) hip resurfacing arthroplasty (HRA), while achieving good results with well-orientated, well-designed components in ideal patients, is contraindicated in women, men with head size under 50 mm, or metal hypersensitivity. These patients currently have no access to the benefits of HRA. Highly crosslinked polyethylene (XLPE) has demonstrated clinical success in total hip arthroplasty (THA) and, when used in HRA, potentially reduces metal ion-related sequelae. We report the early performance of HRA using a direct-to-bone cementless mono-bloc XLPE component coupled with a cobalt-chrome femoral head, in the patient group for whom HRA is currently contraindicated. Methods: This is a cross-sectional, observational assessment of 88 consecutive metal-on-XLPE HRAs performed in 84 patients between 2015 and 2018 in three centres (three surgeons, including the designer surgeon). Mean follow-up is 1.6 years (0.7 to 3.9). Mean age at operation was 56 years (sd 11; 21 to 82), and 73% of implantations were in female patients. All patients were individually counselled, and a detailed informed consent was obtained prior to operation. Primary resurfacing was carried out in 85 hips, and three cases involved revision of previous MoM HRA. Clinical, radiological, and Oxford Hip Score (OHS) assessments were studied, along with implant survival. Results: There was no loss to follow-up and no actual or impending revision or reoperation. Median OHS increased from 24 (interquartile range (IQR) 20 to 28) preoperatively to 48 (IQR 46 to 48) at the latest follow-up (48 being the best possible score). Radiographs showed one patient had a head-neck junction lucency. No other radiolucency, osteolysis, component migration, or femoral neck thinning was noted. Conclusion: The results in this small consecutive cohort suggest that metal-on-monobloc-XLPE HRA is successful in the short term and merits further investigation as a conservative alternative to the current accepted standard of stemmed THA. However, we would stress that survival data with longer-term follow-up are needed prior to widespread adoption. Cite this article : R. B. C. Treacy, J. P. Holland, J. Daniel, H. Ziaee, D. J. W. McMinn. Preliminary report of clinical experience with metal-on-highly-crosslinked-polyethylene hip resurfacing. Bone Joint Res 2019;8:443–450. DOI: 10.1302/2046-3758.810.BJR-2019-0060.R1